Hak dan Kewajiban Desa Adat Sebagai Penerima Hibah Uang Dari Pemerintah Daerah - I Wayan Suambara (Kertha Wicaksana, 2023)
Law Number 23 of 2014 concerning Regional Government does not regulate customary law community units as recipients of monetary grants from the Regional Government. The main objective of this study is to analyze the rights and obligations of the Traditional Village in Bali as a customary law community unit that receives a grant from the Regional Government. Using the normative method by conducting a review of Law number 23 of 2014, Minister of Home Affairs Regulation Number 14 of 2016, Bali provincial regional regulation Number 4 of 2019 concerning Traditional Villages in Bali. The results of the study found that Traditional Villages are entitled to receive grants from the Regional Government which are budgeted through the APBD in accordance with Article 6 paragraph (5) of the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 14 of 2016. Traditional Villages are required to use grant funds obtained from the Regional Government intended to support the achievement of targets programs and activities of the Regional Government in accordance with the urgency and interests of the region. This research is very important as a legal basis for granting money by the Regional Government to Traditional Villages in Bali.